Oil and Gas in the Dynamics of Time and Development - Ainuddin Ainuddin; Muhammad Adam Suryadilaga (Testing Center for Oil and Gas LEMIGAS, 2021)
As a source of energy, industrial raw materials, and foreign exchange for exports, the oil and gas sub-sector has a strategic role in national development. In the period 2020-2024, the management and utilization of oil and gas resources will face several challenges. The purpose of this study is to determine the profile of oil and gas development. The method used and the description in the data is qualitative. The results of this study allow us to statistically understand cluster dynamics. The impact of this research is to map the dynamics of oil and gas as a whole.Â